Contraceptives' Usage Among Undergraduates in Yoruba Ethnic Group of Nigeria: The Roles of Age and Gender - Tosin Emmanuel AKINDUYO (Fakultas keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Kendari, 2024)
This study explored the influence of age and gender on contraceptive use among undergraduates in South-West Nigeria. The primary aim was to examine how contraceptive use among students is moderated by age and gender. The research employed a descriptive survey design, with a sample of 1,200 undergraduates (both male and female, aged 15 and above) selected through a multi-stage sampling method. Data were collected using a self-developed questionnaire, the "Contraceptive Usage Questionnaire" (CUQ), which had a Pearson reliability coefficient (r) of 0.70. Inferential statistics were used for data analysis, with t-tests and ANOVA employed to test the hypotheses. When the ANOVA results indicated significant differences, a Scheffe Posthoc test was conducted to pinpoint the specific areas of significance. The results revealed that gender does not significantly affect contraceptive use among undergraduates, whereas age plays a role in determining usage patterns. Based on these findings, the study recommends that government and university authorities collaborate to introduce a comprehensive sexuality education course to inform students about responsible contraceptive use. Additionally, professional counselors and relevant stakeholders should hold bi-monthly seminars and workshops to educate students on the proper and acceptable use of contraceptives.